Uridine Diphosphate Promotes Rheumatoid Arthritis Through P2Y6 Activation - Wang, Hongxing; Wu, Hui; Fang, Kehua; Chang, Xiaotian (Frontiers in Pharmacology, 2021)
Uridine diphosphate (UDP) is an extracellular nucleotide signaling molecule implicated in diverse biological processes via specific activation of pyrimidinergic receptor P2Y, G Protein-Coupled, 6 (P2Y6). There is very little knowledge about the function and mechanism of UDP in rheumatoid arthritis (RA). METHODS：This study used a quasi-targeted liquid chromatography-mass spectrometry (LC-MS) approach to investigate the unique expression of metabolites in RA synovial fluids (SF)with samples from osteoarthritis (OA) as controls. RA fibroblast-like synoviocytes (FLSs) were collected from synovial tissues (n = 5) and cultured with UDP or MRS2578, a P2Y6 antagonist, and FLSs from OA were used as controls (n = 5). Rats with collagen-induced arthritis (CIA) were injected with UDP, MRS2578 or both (n = 9 for each group). P2Y6 expression was examined using real-time PCR, Western blotting and immunohistochemistry. Cell proliferation, apoptosis and migration of RA FLSs were measured using CCK-8 assay, real-time cell analysis, flow cytometry, wound healing assay and Transwell assay, respectively. The UDP levels in the culture medium, synovial fluid (n = 36) and peripheral blood (n = 36) of RA and CIA rats were measured using a Transcreener UDP Assay. Levels of proinflammatory cytokines were measured using a flow assay. Interleukin-6 (IL-6) levels were measured using ELISA and flow RESULTS：LC-MS analysis detected significantly increased UDP levels in RA SF compared with OA SF, and the level was positively correlated with anticyclic citrullinated peptide (anti-CCP) and rheumatoid factor (RF) levels in RA. The increased UDP concentration was verified in the blood and synovial fluids of RA patients compared with samples from OA patients and healthy volunteers, respectively. UDP stimulated cell proliferation, migration and IL-6 secretion in RA FLSs and inhibited their apoptosis in culture, and MRS2578 inhibited these effects of UDP. UDP injection accelerated CIA and stimulated IL-6 production rather than other proinflammatory cytokines in the rat model, but simultaneous injection of MRS2578 suppressed these effects and alleviated CIA. P2Y6 expression was increased in RA and CIA synovial tissues. CONCLUSION: These results suggest that UDP is highly expressed in RA and stimulates RA pathogenesis by promoting P2Y6 activities to increase IL-6 production.